QUALITY OF CORPORATE SOCIAL RESPONSIBILITY INFORMATION IN INDONESIA - Wiralestari Wiralestari (Jurnal ASET (Akuntansi Riset), 2022)
Currently, social responsibility plays an essential role in the company. Where social responsibility information is a medium to communicate with stakeholders, this information also has a role in gaining the trust of stakeholders due to transparency. The information presented must be relevant and reliable so that it can be trusted. This research was conducted to see how the quality of corporate social responsibility information. The sample of this research is 32 companies that report the company's sustainability report on the sustainability disclosure database. This study uses content analysis that looks at the information contained in the company's sustainability report. GR! 4 and GRI become company standards or guidelines in reporting corporate social responsibility. The results show that companies engaged in finance have higher quality social responsibility information than mining, chemical, and agricultural companies, which directly impact the environment.